294 INTEGRATION OF MUSIC THERAPY WITHIN A MULTIDISCIPLINARY TEAM FOR OLDER ADULTS IN AN ACUTE HOSPITAL. (25th October 2022) - Hayes, R; Cassidy, M; Nevin, R; Walsh, K; Griffin, A; Mealy, B; Herbst, J; Carroll, KM
Abstract: Background: Music Therapy (MT) is an evidence-based intervention in which a music therapist uses music within a therapeutic relationship to achieve targeted goals. Studies show that MT may improve patient communication, cognition and mood, and facilitate rehabilitation by improving motor skills, particularly in those with stroke and Parkinson's disease. We aimed to integrate MT within our geriatric multidisciplinary team (MDT) by: (1) promoting knowledge of MT among MDT staff; and (2) developing and implementing a MT referral pathway for patients. Furthermore, we aimed to assess its overall impact. Methods: Music therapists delivered oral presentations and experiential learning through creative workshops, collaboration and feedback to allied health therapists in our geriatric MDT. Criteria for referrals for MT and a referral pathway were developed. Data on patients who received MT was collated. Results: There were 70 referrals for MT from our MDT. 61% were female, mean age 77 years. Referral sources were occupational therapists (45%), speech therapists (34%), medical social workers (13%), physiotherapists (8%). Patients included those with stroke (41%), general medical conditions (23%), dementia (16%), Parkinson's (11%) and mental health concerns (9%). There were 16 joint MDT sessions and a mean of 5 MT sessions per patient (about 40 minutes in duration). Interventions included: Melodic Intonation Therapy (MIT), singing and vocal exercises, Rhythmic Auditory Stimulation (RAS), Musical Neglect Training (MNT), Therapeutic Instrumental Musical Performance (TIMP), reminiscence and song-writing. Overall, we identified better engagement with rehabilitation and improvements in mood, speech (voice strength and verbal fluency) and upper and lower limb co-ordination. Conclusion: MT was successfully integrated into a geriatric MDT and had beneficial effects on patient mood, speech, communication and motor function. Education of MDT members was crucial in achieving appropriate MT referrals. Joint MDT's also facilitated individualised MT interventions. Findings strongly support our model that incorporates MT within an MDT.